In what form have black people been represented in Science didactic books used in Santa Maria-RS public school? (Research, Society and Development, 2018)
This article aims to investigate ethnic racial representations in two collections of Science and Nature Science textbooks, initial series, approved by the National Program of Didactic Book (PNLD), created in 1985, fulfilling the duty assumed by the State to provide didactic material for all accessing public education. Through observation, identification and categorization, 313 images were analyzed in textbooks. We find a diversity of representations of individuals and characters presented, albeit without many ethnic cultural distinctions.